The public–private governance regime on sustainable ship recycling: An in‐depth analysis. Issue 2 (12th June 2022) - Glinski, Carola
Abstract: To address global sustainability issues, legal frameworks increasingly build upon private governance contributions such as private standardization and/or private certification. This is particularly true for ship recycling under the Hong Kong Convention and its European implementation, the Ship Recycling Regulation. After a brief introduction into the old public law approach as compared with the new public–private governance structure, the article offers a critical in‐depth analysis of the effectiveness of the new governance structure based upon private certification. It thereby draws from research in, and experience with, traditional ship classification as well as other certification systems in European Union law. The article concludes that, despite laudable elements, the governance structure of the Ship Recycling Regulation has some important gaps and does not remedy the classical conflicts of interest of certification organizations. Among others, it should be complemented with a liability regime.